Isolation, Characterization, and Evaluation of Native Rhizobacterial Consortia Developed From the Rhizosphere of Rice Grown in Organic State Sikkim, India, and Their Effect on Plant Growth - Sherpa, Mingma Thundu; Sharma, Laxuman; Bag, Niladri; Das, Sayak (Frontiers in Microbiology, 2021)
Eight rhizospheric bacteria were isolated and identified from the organic paddy fields of Sikkim, India i.e. Pseudomonas kribbensis KSB, Burkholderia cenocepacia SRD, Kosakonia oryzendophytica YMA7, Pseudomonas rhodesiae SRB, Bacillus sp. ARA, Paenibacillus polymyxa COW3, Bacillus aryabhattai PSB2, and Bacillus magaterium PSB1. They showed plant growth promoting attributes in rice and has bio-control potential against phytopathogen Colletotrichum gloeosporioides of large cardamom (Amomum subulatum). Burkholderia cenocepacia SRD showed effective production of phyto-hormone indole acetic acid, ammonia, phosphate, potassium, and also possessed nitrogen fixation activity. It showed antagonistic activity against two other plant pathogen fungi, Curvularia eragrostidis and Pestalotiopsis sp., under in vitro conditions. Moreover, the liquid bacterial consortium was prepared using the bacterial strains SRB, PSB1, COW3 (Consortia-1); PSB2, SRD, COW3 (Consortia 2); and COW3, KSB, and YMA7 (Consortia 3) to increase the growth and yield of rice plant under organic farming conditions. Our field-based studies showed that the Consortia-3 had the highest plant growth-promoting activity. Consortia-3 demonstrated better agronomic parameter performance measured by host plant root length (9.5 cm), the number of leaflets per plants (5.3), grain per panicle (110.6), test grain weight (27.4 g), dry root weight per plant (0.73 g) and total dry biomass per plant (8.26 g) respectively.